2018
DOI: 10.3846/tede.2018.5582
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Sustainability Into Supplier Selection: A Grey-Based Topsis Analysis

Abstract: Sustainable supplier selection plays an important role in sustainable supply chain management operations and implementation. In this paper a novel formal modeling approach is conceptually developed and presented to address sustainable supplier selection. Grey theory and TOPSIS, a distance based multiple criteria method, are used for the integration and evaluation of sustainable supplier performance for sustainable supplier selection. From a research perspective, TOPSIS is improved to more effectively deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 32 publications
0
21
0
5
Order By: Relevance
“…This can be a safe ground for mining similar matters in other patent sections that are irrelevant to electronics or IT. Other than patentography, the possible analytical targets of application include, for example, data sets which pertain to supply chain management (SCM) [31], aeronautics [32], or engineering [33] (e.g., the building information management (BIM) data), as they are quality data sets as patent databases. Finally, even though the proposed methodological flow only utilises 'data mining' and completely ignores the perspectives of 'mind mining' for data-driven decision making (DDDM, or D 3 M) [34], it should also pave the way for relevant future research.…”
Section: Discussionmentioning
confidence: 99%
“…This can be a safe ground for mining similar matters in other patent sections that are irrelevant to electronics or IT. Other than patentography, the possible analytical targets of application include, for example, data sets which pertain to supply chain management (SCM) [31], aeronautics [32], or engineering [33] (e.g., the building information management (BIM) data), as they are quality data sets as patent databases. Finally, even though the proposed methodological flow only utilises 'data mining' and completely ignores the perspectives of 'mind mining' for data-driven decision making (DDDM, or D 3 M) [34], it should also pave the way for relevant future research.…”
Section: Discussionmentioning
confidence: 99%
“…Common supply processes (such as ordering and delivery of goods) involve not only financial factors but also timing-related aspects, which directly affect supplier satisfaction (Maunu, 2003). Environmental factors, such as increased reputation, avoiding environmental fines and saving environmental pollution control costs, also need to be considered in evaluating green supply processes (Bai and Sarkis, 2018). Most importantly, green supply processes can help suppliers to maintain a stable long-term cooperative relationship with the buyers in the context of GSCM.…”
Section: Green Supply Processesmentioning
confidence: 99%
“…Hence, satisfaction of suppliers on the economic and environmental dimensions is linked to the quality of the buyer-supplier relationship and to the degree of value creation between them (Vos et al, 2016). Although a number of articles are reported in the literature on evaluating suppliers' performance from the buyer perspective (Bai, Kusi-Sarpong, Badri Ahmadi and Sarkis, 2019;Bai and Sarkis, 2018), nowadays, buyers are focusing on building long-term and fair cooperation with their suppliers. Hence, it is essential for the buying firms to consider green supplier satisfaction in evaluating suppliers' performance.…”
Section: Introductionmentioning
confidence: 99%
“…In a bid to minimise cost and improve the quality of services, manufacturing companies have benefited from outsourcing resources and many of their manufacturing processes to other companies. This resolution has presented paint manufacturing companies with numerous unfamiliar challenges [1]. An analysis by Accenture Consulting revealed that 80 per cent of the companies that responded drew their services and inventory from third-party providers, and allocated more than half of their funds to outsourcing [2].…”
Section: Introductionmentioning
confidence: 99%
“…This has been motivated by the need to protect natural resources and to maintain a balance between the profits generated and the social duties of companies. The identification and selection of an ideal and sustainable supplier can give a company competitive advantage in reducing operating costs, improving the quality of its goods, and being able to to offer improved services to its clientele [1]. The acknowledged steps in evaluating and selecting a sustainable supplier have expanded greatly from a peripheral view based only on a price orientation.…”
Section: Introductionmentioning
confidence: 99%